Gene Expression Associated with Early and Late Chronotypes in Drosophila melanogaster - Pegoraro, Mirko; Picot, Emma; Hansen, Celia N.; Kyriacou, Charalambos P.; Rosato, Ezio; Tauber, Eran (Frontiers in Neurology, 2015)
The circadian clock provides the temporal framework for rhythmic behavioural and metabolic functions. In the modern era of industrialization, work and social pressures, the clock function is often jeopardized, resulting in adverse and chronic effects on health. Understanding circadian clock function, particularly individual variation in diurnal phase preference (chronotype), and the molecular mechanisms underlying such chronotypes may lead to interventions that could abrogate clock dysfunction and improve human (and animal) health and welfare. Our preliminary studies suggested that fruitflies, like humans, can be classified as early rising ‘larks’ or late rising ‘owls’, providing a convenient model system for these types of studies. We have identified strains of flies showing increased preference for morning emergence (Early or E) from the pupal case, or more pronounced preference for evening emergence (Late or L). We have sampled pupae the day before eclosion (4th day after pupariation) at 4 h intervals in the E and L strains, and examined differences in gene expression by RNAseq. We have identified differentially expressed transcripts between the E and L strains which provide candidate genes for studies of Drosophila chronotypes and their human orthologues.